Sentidos do trabalho para professores do ensino médio em uma escola em bairro com alto índice de criminalidade - LIMA, Steffi Greyce De Castro (2020)
The teaching worker, especially in basic education at public schools, has many challenges that require physical, psychological and social skills. In addition to the difficulties common to the profession, some experience working at neighborhood considered violent, which also influenced the work. In this research, we sought to analyze the meaning of work for high school teachers from a public school located in the neighborhood with the highest rate of lethal and intentional violent crimes (CVLI) in São Luís. Interviews were conducted with a semi-structured script and from the testimonies, it was possible to carry out discussions about perceptions about violence in general and about community violence in the neighborhood, the influences of violence on school dynamics, the meaning of work for these teachers and the elements of pleasure and suffering in the teaching work in this place. It was observed that the teaching work for the research participants is still constituted by meaning and, despite the difficulties, considered pleasurable due also to the meaning that this work has. There are dynamics of pleasure and suffering, but the present suffering does not overlap with pleasure. Violence in the community is recognized as a present factor and perceived by teachers, especially drug trafficking; the narratives show feelings of fear, but the school space is considered safe and pleasant due mainly to the relationships built there, which facilitates work in space.